Studies on authorship in historical keyboard music - Cassia, Cristina 1978- (Routledge, 2024)
"Authorship is a prescient issue for historical musicology and musicians more widely, while some controversies concerned with major figures have even reached wider consciousness. Scholars have clarified some of the issues at stake in recent decades, such as the places of borrowing and arranging in the creative process and the wider cultural significance of these practices. The discovery of new sources and methodologies has also opened up opportunities for reassessing specific authorship problems. Drawing upon this wider musicological literature as well as insights from other disciplines, such as intellectual history and book history, this book aims to build on what has already been achieved by focusing on keyboard music. The nine chapters cover case studies of authorship problems, the socioeconomic conditions of music publishing, the contributions of composers, arrangers, copyists and music publishers in creating notated keyboard compositions, the functions of attribution and ascription, and how the contexts in which notated pieces were used affected concepts of authorship at different times and places"--
Keywords: Geschichte 1430-1803; Autorschaft; Tasteninstrumentenmusik; Keyboard instrument music / History and criticism; Music / Attribution; Instrument à clavier, Musique d' / Histoire et critique; Musique / Attribution; Keyboard instrument music; Criticism, interpretation, etc; Aufsatzsammlung